Tailoring the synthesis of graphene and other 2D materials towards applications - Babenko, V (2016)
This thesis focuses on using Chemical Vapour Deposition (CVD) technique to produce various classes of flat 2D materials and also their three-dimensional architectures. Graphene, hexagonal boron nitride (hBN) and tungsten disulfide (WS2) are the main examples presented in the study: a conductor, an insulator and a semiconductor respectively. Such materials are elementary "building blocks" in a variety of applications. Many novel advances to CVD synthesis of 2D materials are identified, developed and discussed in this thesis.